2014
DOI: 10.1186/2008-2231-22-45
|View full text |Cite
|
Sign up to set email alerts
|

Effect of myrtle fruit syrup on abnormal uterine bleeding: a randomized double-blind, placebo-controlled pilot study

Abstract: BackgroundMyrtle (Myrtus communis L.) has been used in the Iranian Traditional Medicine as a treatment for abnormal uterine bleeding-menometrorrhagia. The main aim of this study is to evaluate the effect of myrtle fruit syrup on abnormal uterine bleeding-menometrorrhagia.MethodsA randomized, double-blind, placebo-controlled pilot study was conducted on 30 women suffering from abnormal uterine bleeding-menometrorrhagia. Treatment comprised of giving 15 ml oral myrtle syrup daily (5 ml three times a day) for 7 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…The total score of MQ varied from zero to 100 and a lower score means a better quality of life. The validity and reliability of this questionnaire have been confirmed in other studies in Iran [35,36].…”
Section: Measurementssupporting
confidence: 75%
See 1 more Smart Citation
“…The total score of MQ varied from zero to 100 and a lower score means a better quality of life. The validity and reliability of this questionnaire have been confirmed in other studies in Iran [35,36].…”
Section: Measurementssupporting
confidence: 75%
“…In the past, tyramine and choline were responsible for controlling the bleeding by the plant. Todays, new researches have shown that other substances that are not fully recognized may be responsible for such an effect [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Anyway, the contractile and hemostatic nature of this drug cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Qaraaty et al . () reported a randomized, double‐blind, placebo‐controlled pilot study in Iran conducted on 30 women of reproductive age suffering from AUB‐E. M. communis is a species of the Myrtaceae family known under the Persian name ‘mourd’ or ‘aass’.…”
Section: Resultsmentioning
confidence: 97%
“…The results were similar to the findings of this study. In the study carried out by Qaraaty et al, the duration of bleeding and the number of pads used as well as the quality of life score decreased in patients with abnormal uterine bleeding through the prescription of "Myrtle syrup" 30 . In Qaraaty's study, "Myrtle syrup" was taken 7 days every month, but in this study, "Quince paste" was taken for the entire month.…”
Section: Discussionmentioning
confidence: 99%